EVALUASI WEBSITE KAMPUS MENGGUNAKAN METODE SYSTEM USABILITY SCALE (SUS) - Ahmad Ridoh; Deka Ismi Mori Saputra (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2026)
Abstract The official website of a higher education institution is one of the most important means of communication and information services for the academic community and the general public. The usability quality of a campus website directly affects the ease with which users can access the information they need. This study aims to evaluate the usability level of the official website of Universitas Muhammadiyah Muara Bungo (UMMUBA) using the System Usability Scale (SUS) method as a basis for improving campus digital information services. The research used a descriptive quantitative approach with data collection through observation, questionnaires, and documentation. The research respondents consisted of 40 people including students, lecturers, administrative staff, and the general public who were selected using purposive sampling technique. The instrument used was the SUS questionnaire consisting of 10 statements with a Likert scale of 1 to 5. Data were analyzed using the standard SUS score calculation formula and categorized based on three interpretation dimensions, namely Acceptability, Grade Scale, and Adjective Rating. The results showed that the official UMMUBA website obtained an average SUS score of 62.75, which falls in the Marginal High category in the Acceptability dimension, grade C on the Grade Scale, and the good category on the Adjective Rating. These results indicate that the UMMUBA website still requires improvement in terms of navigation, interface consistency, and information access speed. The novelty of this research lies in the formal usability evaluation of a regional university website that has never been formally conducted, so that the results can serve as a strategic reference for UMMUBA management in improving the quality of campus digital information services. Keywords: University Website; Usability; SUS; System Evaluation; User Experience.